The VE Development Policy Meets The High-Quality Human Resources of Ho Chi Minh City - DangNguyen, AnLong (Randwick International of Social Science Journal, 2024)
Vocational Education (VE) level training elementary, intermediate, college, and other vocational training programs. Ho Chi Minh City (HCMC) has 393 VE establishments, including 57 colleges, in these 12 colleges under the People’s Committee of HCMC, 64 intermediate schools, 24 VE centers - continuing education, 248 VE centers, and VE establishments. In addition, there are 67 universities located in the area including Saigon University under the People’s Committee of HCMC. HCMC is the area with the largest concentration of VE establishments in the country; at the same time, it is a place to provide quality human resources for the City’s socio-economic development. Innovate and improve the quality of VE, and implement strong breakthrough solutions associated with improving the quality of human resources, especially H-Q HR, following labor market needs, meeting the requirements of development, and international integration have been the goals throughout Party Committee and people of HCMC in the years. This article clarifies the role of VE in training high-quality human resources (H-Q HR); the importance of VE policy, and the current situation and proposes some solutions to improve VE development policies to meet the H-Q HR of HCMC today.